Voicing fluid voices: reflections of the multivalence of voice in Miriam Makeba's art and life. Issue 1 (2nd January 2019) - Muyanga, Neo
Abstract : The article examines voice and voicing in translation processes in music, using on the one hand the example of Miriam Makeba, and on the other hand, features of African choir, in order to develop a broader argument about the musical and political significance of the multivalence of voice. The article begins with a re-valuation of some of the contributions of Miriam Makeba and their relevance to contemporary concerns of the twenty-first century, specifically to societies such as South Africa. It reflects on some of the salient revelations in her autobiography as well as on her music, her style and her politics. I argue that Makeba deployed voice as a sophisticated vehicle of translation with a vision of multivalent and plural futures. In the final section of the article, I reflect on my own artistic involvements and experiments using choir, both in translating African choral traditions to contemporary European performance contexts, as well as in the African repurposing of Western choral elements. My interest in voice and embodied translation is not merely technical, but reflects a political concern and vision, which at its core, strives towards a recalibration and reconstitution of concepts of Africanity, not as rigid and exclusionary, but rather as multi-valent and pluriversal.